2000
DOI: 10.1111/j.1749-6632.2000.tb06767.x
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Accumulation along the Western Nankai Trough

Abstract: A one‐dimensional gas hydrate accumulation model is developed to simulate the existence of hydrate in the Nankai Trough margin, where the total organic carbon content is extremely low. In order to study the accumulation of gas hydrate along a seismic profile, our model assumes an initial 1000 m thick turbidite sedimentation at the trench axis, and then the sediment experiences tectonic uplift to form the Nankai accretionary prism. Methane generated by microbial processes during the sedimentation is partly trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Pore water flow can be focused by layers of high permeability in sediments (Hovland et al, 1997;Aoki et al, 2000;Flemings et al, 2002). Lateral flow steered by sediment permeability predicts expulsion of fluid near the base of the continental slope off New Jersey, consistent with the observed patterns of porewater seeps, and leading to nucleation of landslides from the base of the slope, consistent with the observation of submarine canyons on continental margins (Dugan and Flemings, 2000).…”
Section: Aqueous Flowsupporting
confidence: 58%
See 1 more Smart Citation
“…Pore water flow can be focused by layers of high permeability in sediments (Hovland et al, 1997;Aoki et al, 2000;Flemings et al, 2002). Lateral flow steered by sediment permeability predicts expulsion of fluid near the base of the continental slope off New Jersey, consistent with the observed patterns of porewater seeps, and leading to nucleation of landslides from the base of the slope, consistent with the observation of submarine canyons on continental margins (Dugan and Flemings, 2000).…”
Section: Aqueous Flowsupporting
confidence: 58%
“…Seismic studies at Blake Ridge have observed the presence of bubbles along faults in the sediment matrix (Taylor et al, 2000). Faults have been correlated with sites of methane gas emission from the sea floor (Aoki et al, 2000;Zuhlsdorff et al, 2000;Zuhlsdorff and Spiess, 2004). Seismic studies often show "wipeout zones" where the bubble zone beneath the hydrate stability zone is missing, and all of the layered structure of the sediment column within the stability zone is smoothed out.…”
Section: Gas Migrationmentioning
confidence: 99%
“…The host sediment is assumed to be weak and unconsolidated sediment, with S H = 0.1. Such HBS are typical of a widely occurring type of hydrate deposits (Moridis and Kowalsky 2006;Aoki at al. 2000), both in terms of texture (soft and structurally weak muds and clays are common at the ocean floor, with the cementing hydrates providing the only structural strength of the HBS) and hydrate saturation (Klauda and Sandler 2005).…”
Section: The Numerical Simulatormentioning
confidence: 97%
“…Such a HBS is typical of a widely-occurring type of hydrate deposits 14,24 both in terms of texture (soft and structurally weak muds and clays are common at the ocean floor, with the cementing hydrates providing the only structural strength of the HBS) and hydrate saturation 25 . In this case we investigate the geomechanical behavior of oceanic HBS at or near the ocean floor, in which anchors or foundation of structures (such as offshore platforms) are installed.…”
Section: Problem 3: Loading Caused By the Weight Of Structures Placedmentioning
confidence: 99%